2017
DOI: 10.1111/pde.13049
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Half‐Head Comparison of 1% Anthralin Ointment in Children with Alopecia Areata

Abstract: Anthralin 1% is an effective therapy for AA and should be continued at least 9 months. At 9 months of topical anthralin therapy, the patients with at least a 50% reduction in their pretreatment SALT scores should continue the same treatment for at least 1 year. Anthralin is safe in children with chronic, severe, treatment-refractory, extensive AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
1
24
0
3
Order By: Relevance
“…In an uncontrolled study, 25% showed cosmetically acceptable hair growth; however, it failed to show any therapeutic benefits in 11 AT cases . In a recent half‐head study of pediatric patients, anthralin showed a better therapeutic effect on the treated side than the untreated side . In a RCT comparing anthralin and azelaic acid, both showed the comparable effect .…”
Section: Second‐line Therapiesmentioning
confidence: 99%
“…In an uncontrolled study, 25% showed cosmetically acceptable hair growth; however, it failed to show any therapeutic benefits in 11 AT cases . In a recent half‐head study of pediatric patients, anthralin showed a better therapeutic effect on the treated side than the untreated side . In a RCT comparing anthralin and azelaic acid, both showed the comparable effect .…”
Section: Second‐line Therapiesmentioning
confidence: 99%
“…25,61 However, both 5% minoxidil and 1-2% topical antraline could be prescribed in these patients. 62 In severe cases of AA, topical immunotherapy (diphenylcyclopropenone), has been used. Although corticosteroid pulse therapy has shown lower adverse effects at low doses.…”
mentioning
confidence: 99%
“…There is growing evidence of safety and efficacy in treatment of recalcitrant pediatric alopecia areata with emphasis on very thorough washing of any anthralin residue to minimize skin irritation (Ngwanya, ; Özdemir, ; Wu, ).…”
Section: Treatment Strategies In Special Populationsmentioning
confidence: 99%
“…CCS of mild and midpotency are preferred over potent ones. Calcipotriol is not to be applied for children There is growing evidence of safety and efficacy in treatment of recalcitrant pediatric alopecia areata with emphasis on very thorough washing of any anthralin residue to minimize skin irritation (Ngwanya, 2017;Özdemir, 2017;Wu, 2018).…”
Section: Childrenmentioning
confidence: 99%